Dental abnormalities in children after chemotherapy treatment for acute lymphoid leukemia - Minicucci, E. M.; Lopes, L. F.; Crocci, A. J. (Elsevier B.V., 2003)
The frequency of dental abnormalities, such as delayed dental development, microdontia, hypoplasia, agenesis, V-shaped root and shortened root was evaluated in 76 acute lymphoblastic leukemia (ALL) pediatric patients who had been off chemotherapy for 6 months. These children had been subjected to one of the three Brazilian Protocols or the BFM86 Protocol. The patients were divided into three groups: Group I (GI; high risk) treated with one of the three Brazilian Protocols who received high-dose chemotherapy, intensive maintenance and cranial radiotherapy; Group II (GII; low risk) who were also treated with one of the three Brazilian Protocols using low-intensive chemotherapy with no radiotherapy; and Group III (GIII) based on the BFM86 Protocol.Of 76 children, 13 showed no dental abnormalities (8 were at the age of tooth formation). The remaining 63 children (82.9%) showed at least one dental anomaly.The abnormalities were probably caused by the type, intensity, frequency of the treatment and age of the patients at ALL diagnosis and this might have important consequences for the children's dental development. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: odontogenesis drugs effects; antineoplastic agents adverse effects; chemotherapy dental abnormalities; late effects of ALL treatment